Novel and successful treatment of generalized arterial calcification of infancy in a patient with previously undescribed mutation in ENPP1. (September 2022) - Weingarten, Angela J.; Muller, Aaron; Langman, Craig; Groner, Abraham
Abstract: Newborn infants with generalized arterial calcification of infancy are at a substantial risk of sudden cardiac death. Treatment with bisphosphonates while helpful does not guarantee a favorable outcome. Herein we report a case of generalized arterial calcification of infancy from fetal diagnosis through childhood. The patient exhibited a previously unreported variant in the ENPP1 gene. Newborn echocardiogram and CT imaging showed extensive calcifications throughout the coronary arteries and aortic arch. Treatment started immediately after birth. Long-term follow-up has demonstrated disease regression. Early recognition and treatment were instrumental in reversing this infant's disease. Successful treatment included the previously reported use of pamidronate but with the novel inclusion of acetazolamide and Similac PM 60/40® (low calcium, low phosphate infant formula). Highlights: Generalized arterial calcification of infancy is a rare and frequently fatal disease in infants. Treatment with bisphosphonates helps many but not all children with the disease. Addition of specialized formula and acetazolamide to bisphosphonate therapy may improve outcomes.